2019
DOI: 10.2106/jbjs.18.01307
|View full text |Cite
|
Sign up to set email alerts
|

“Found Down” Compartment Syndrome

Abstract: Background: With the worsening of the opioid epidemic, there has been an increasing number of cases in which patients are “found down” following a drug overdose and develop a crush injury resulting in muscle necrosis, rhabdomyolysis, and elevated compartment pressures in a unique presentation of compartment syndrome. The purpose of the present study is to summarize our experience at a trauma center in a region with a high endemic rate of opiate abuse to provide guidance for the management of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 6 publications
1
25
1
Order By: Relevance
“…[6][7][8][9][10] In a case series of 30 patients found down after opioid overdose, the authors suggested poor function on presentation did not improve despite fasciotomy. 11 Our case suggests the sedative effects of Kratom because of its action on the mu-receptor resulted in a similar case of pressure necrosis and compartment syndrome. The respiratory depression that can occur in overdose is thought to be due to partial mu-agonist activity.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…[6][7][8][9][10] In a case series of 30 patients found down after opioid overdose, the authors suggested poor function on presentation did not improve despite fasciotomy. 11 Our case suggests the sedative effects of Kratom because of its action on the mu-receptor resulted in a similar case of pressure necrosis and compartment syndrome. The respiratory depression that can occur in overdose is thought to be due to partial mu-agonist activity.…”
Section: Discussionmentioning
confidence: 61%
“…Rhabdomyolysis is not generally associated with Kratom use, but there are numerous reports of opioids, sedative-hypnotics, ethanol, and carbon monoxide resulting in prolonged periods of immobilization with rhabdomyolysis caused by pressure necrosis 6–10 . In a case series of 30 patients found down after opioid overdose, the authors suggested poor function on presentation did not improve despite fasciotomy 11 . Our case suggests the sedative effects of Kratom because of its action on the mu-receptor resulted in a similar case of pressure necrosis and compartment syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…2 In the United States, prolonged immobilization after alcohol or opioid abuse is a common etiology of compartment syndrome. [3][4][5][6][7] In our cases, we have found that other illicit substances such as benzodiazepines, amphetamines and synthetic cannabinoids, which are less commonly described with compartment syndrome can also cause this presentation.…”
Section: Introductionmentioning
confidence: 95%
“…Depressants, including alcohol and heroin, have been described in the literature in multiple case reports as direct causes of obtundation and immobility leading to compartment syndrome. [3][4][5][6][7] Other substances such as synthetic cannabinoids or K2 have been less frequently described as being associated with compartment syndrome. In one study from Turkey, Ergul et al describes six cases in which synthetic cannabinoids were directly linked to cases of renal failure, rhabdomyolysis and compartment syndrome.…”
Section: Etiologymentioning
confidence: 99%
“…Although AECS is often caused by trauma, nontraumatic causes for compartment syndrome are becoming more common and possibly linked to the increase in substance use disorders. 1 Approximately 20.3 million Americans are reported to have a substance use disorder. 2 It is estimated that 14.8 million people suffer from alcohol use disorder and 8.1 million have illicit drug use disorder.…”
Section: Introductionmentioning
confidence: 99%